APLIKASI JARINGAN SENSOR NIRKABEL UNTUK PEMANTAUAN KADAR PARTIKULAT UDARA - , TRI ALHUDI J; , Ardhi Wicaksono S.S.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wireless Sensor Networks ( WSN ) is a network system consisting of sensor nodes, routers and sinks ( coordinator ). These devices are connected and can exchange data. Wireless sensor networks are often used for monitoring and controlling an object in various fields. This final project applying wireless sensor network system to determine the level of particulate content of the air. WSN topology used is a cluster tree consisting of 2 sensor nodes, 1 router and 1 sink (coordinator) who will communicate with each other using the module nRF24L01 transceiver to transmit data from the sensor readings. Air particulate detected by dust DS501A sensor. All systems are processed by AVR Atmega mikrokontrol 328A . Then the results are displayed on the LCD character display interface and a column shaped graph . The results obtained from this system value of 0.004 ug/m3 particulate levels at each percent ratio and threshold limit value (TLV) of 0.08 ug/m3 with data retrieval time for 30 seconds. This system needs to be development of the network and particulate readings to be applied in a real environment.